2011
DOI: 10.1007/s10709-011-9562-4
|View full text |Cite
|
Sign up to set email alerts
|

Genes versus phenotypes in the study of speciation

Abstract: Despite persistent debate on the nature of species, the widespread adoption of Mayr's biological species concept has led to a heavy emphasis on the importance of reproductive isolation to the speciation process. Equating the origin of species with the evolution of reproductive isolation has become common practice in the study of speciation, coincident with an increasing focus on elucidating the specific genetic changes (i.e.-speciation genes) underlying intrinsic reproductive barriers between species. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 113 publications
3
71
0
Order By: Relevance
“…The putative sex-linked inversion we document in Ostrinia appears consistent with the large-effect, multicomponent prediction of chromosomal rearrangement models of speciation. First, multiple 'speciation phenotypes' (Shaw and Mullen, 2011) in ECB have known sex-linked factors, including male pheromone response and diapause timing (McLeod, 1978;Dopman et al, 2004;Wanner et al, 2010;Ikten et al, 2011). Second, a recent study indicated that large isolation effect sizes are common between ECB strains (RI ⩾ 0.5 for 4 of 7 forms of isolation; Dopman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The putative sex-linked inversion we document in Ostrinia appears consistent with the large-effect, multicomponent prediction of chromosomal rearrangement models of speciation. First, multiple 'speciation phenotypes' (Shaw and Mullen, 2011) in ECB have known sex-linked factors, including male pheromone response and diapause timing (McLeod, 1978;Dopman et al, 2004;Wanner et al, 2010;Ikten et al, 2011). Second, a recent study indicated that large isolation effect sizes are common between ECB strains (RI ⩾ 0.5 for 4 of 7 forms of isolation; Dopman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is a debate whether inability to interbreed is only an integrated signature effect, the by-product of selection, that is the accumulated loss of reproductive compatibility, or it is the primary cause of speciation, the creator, the mechanism of selection. Phenotypic divergences between incipient species suggest causal interactions between divergent trait and gene flow restrictions during speciation (Shaw & Mullen 2011). Evolution works by screening phenotypes rather than genotypes.…”
Section: Is Paramere a Speciation Super Trait?mentioning
confidence: 99%
“…Which diverging phenotypes involved, redundant or neutral in suppressing gene flow? Speciation phenotypes are those traits whose divergence contributes to a reduction of gene flow (Shaw & Mullen 2011). Phenotypic divergence, as a proximate instrument of speciation in sympatry or allopatry or via founder effect or reinforcement, rarely studied systematically.…”
Section: Is Paramere a Speciation Super Trait?mentioning
confidence: 99%
See 1 more Smart Citation
“…Speciation phenotypes are those traits whose divergence contributes to a reduction of gene flow (Shaw & Mullen 2011). Speciation traits are expressed phenotypes of speciation genes.…”
Section: Speciation Traits: Magic or Super?mentioning
confidence: 99%